البحث عن الذات في رواية "ناقة الله " لإبراهيم الكوني - (:unkn) unknown (My University, 2023)
Summary: The study dealt with the search for the self in the novel God's Koni. This research consisted of an -Camel by the writer Ibrahim Al introduction and two chapters, which are as follows The introduction paved the way for our research, in which we Koni (his birth, upbringing....) as well as his -touched on Ibrahim al works, as well as a summary of the novel. As for the first chapter, which in turn was divided into two sections : A: The novel: the concept (language, terminology) and the emergence of the Western, Arab, and Libyan novel. B: The self: its concept, characteristics, and dimensions. As for the second chapter, we studied the manifestations of the self in the novel, then the significance of the title, characters, time, and place ---------------------- ملخص : تناولت الدراسة البحث عن الذات في رواية ناقة الله للكاتب إبراهيم الكوني ،حيث جاء هذا البحث عبارة عن مدخل وفصلين وهي كالآتي : حيث جاء المدخل ممهدا لبحثنا تطرقنا فيه إلى إبراهيم الكوني (مولده ، نشأته ....) كذلك أعماله وكذلك ملخص الرواية أما الفصل الأول والذي قسم بدوره إلى قسمين : أ: الرواية : مفهوم (لغة ،اصطلاحًا ) ونشأة الرواية الغربية والعربية والليبية . ب: الذات : مفهومها وخصائصها وأبعادها ، أما الفصل الثاني درسنا فيه تجليات الذات في الرواية ، ثم دلالة العنوان والشخصيات والزمان والمكان . ------------------------------------- résumé : L'étude a porté sur la recherche de soi dans le roman Le Koni. Cette recherche -chameau de Dieu de l'écrivain Ibrahim Al comprenait une introduction et deux chapitres qui sont les suivants : L'introduction a ouvert la voie à notre recherche, dans laquelle Koni (sa naissance, son éducation....)-nous avons abordé Ibrahim al ainsi que ses œuvres, ainsi qu'un résumé du roman. Quant au premier chapitre, qui à son tour était divisé en deux sections: A: Le roman : le concept (langue, terminologie) et l'émergence du roman occidental, arabe et libyen. B: Le soi: son concept, ses caractéristiques et ses dimensions Quant au deuxième chapitre, nous avons étudié les manifestations du soi dans le roman, puis la signification du titre, des personnages, de l'époque et du lieu.
Keywords: God's camel; the novel; manifestations of the self.; ناقة الله ، الرواية ، تجليات الذات; le chameau de Dieu; le roman; les manifestations de soi.